2014
DOI: 10.1080/10408398.2011.625574
|View full text |Cite
|
Sign up to set email alerts
|

Cranberry and Recurrent Cystitis: More than Marketing?

Abstract: Epidemiologic studies indicate that millions of people suffer from recurrent cystitis, a pathology requiring antibiotic prophylaxis and entailing high social costs. Cranberry is a traditional folk remedy for cystitis and, which, in the form of a variety of products and formulations has over several decades undergone extensive evaluation for the management of urinary tract infections (UTI). The aim of this retrospective study is to summarize and review the most relevant and recent preclinical and clinical studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 128 publications
(47 citation statements)
references
References 80 publications
0
45
0
2
Order By: Relevance
“…However, the increased employment of alternative and complementary medicines requires a lot of attention from the scientific community in order to evaluate the effectiveness and safety of herbal preparations since studies have cast some doubts on whether their use is really producing an alternative to synthetic drugs (5,36,37). Although numerous in vitro and in vivo studies have suggested a protective effect of green-tea polyphenols against development of prostate cancer, to date this has not been unequivocally demonstrated in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the increased employment of alternative and complementary medicines requires a lot of attention from the scientific community in order to evaluate the effectiveness and safety of herbal preparations since studies have cast some doubts on whether their use is really producing an alternative to synthetic drugs (5,36,37). Although numerous in vitro and in vivo studies have suggested a protective effect of green-tea polyphenols against development of prostate cancer, to date this has not been unequivocally demonstrated in humans.…”
Section: Discussionmentioning
confidence: 99%
“…A chemoprevention approach in patients with high risk of PCa can be proposed in order to reduce the disease progression rate. It is known that natural product can be used to prevent and/or alleviate several health disorders (2-4), including those affecting the urinary tract (5). Moreover, regular dietary habits coupled with a healthy lifestyle may protect against certain types of cancer (6,7), including PCa.…”
mentioning
confidence: 99%
“…The cancer protective effects of vegetables and fruits may be due to the presence of bioactive molecules acting through different mechanisms including the following: inhibition of carcinogen activation, stimulation of carcinogen detoxification, scavenging of free radical species, control of cell-cycle progression, inhibition of cell proliferation, induction of apoptosis, inhibition of oncogene activity of, inhibition of angiogenesis and metastasis, and inhibition of hormone or growth-factor activity [4,9,10,11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…81,82 According to recent meta-analyses, overall UTI recurrence rates over 1 year could not be reduced by various cranberry products. This is also true for the following separately evaluated subgroups: elderly, pediatric patients, patients with neurogenic bladder, and patients with chronic indwelling urinary catheters.…”
Section: Resultsmentioning
confidence: 99%